2022
DOI: 10.1111/jcms.13432
|View full text |Cite
|
Sign up to set email alerts
|

Policy Learning and European Integration

Abstract: way of doing integration'a point that was not lost in classic theories of European integration (Ferrara and Kriesi, 2022). A crisis provides a formidable threat to integration. But it also creates a decision-making window of opportunity wider than normal-times windows. How the EU approaches this opportunity is crucial: it can be a disaster or a positive discontinuity, a leap into further integration. After all, 'Europe will be forged in crisis' famously wrote Jean Monnet in his Mémoires (1976). Can we then loo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…It occurs when policy actors “uptake new information about how to address a problem” that has been recognized as significant (Crow et al, 2023, p. 13). Importantly, “learning is a possible result of the ‘way of managing and responding to crises’” (Radaelli, 2022). In this article, as we observe short‐term learning occurrences happening during a crisis, the focus is on the process of learning (i.e., through which mechanisms and in which platforms did policy‐makers learn during pandemic management), and less on the results of learning.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…It occurs when policy actors “uptake new information about how to address a problem” that has been recognized as significant (Crow et al, 2023, p. 13). Importantly, “learning is a possible result of the ‘way of managing and responding to crises’” (Radaelli, 2022). In this article, as we observe short‐term learning occurrences happening during a crisis, the focus is on the process of learning (i.e., through which mechanisms and in which platforms did policy‐makers learn during pandemic management), and less on the results of learning.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…These opportunities have the capacity of becoming turning points (much like the Brexit referendum) changing power dynamics, agendas and the applicability of existing solutions, shifting the boundaries of the EU's own comfort zone. Radaelli (2022) in the Annual Review annual lecture suggested that lessons learned from one crisis should feed into learning mechanisms preparing a political system for the next one. To that end, the multiplicity of crises not only can change the rules of the game at the EU level, as well as the degrees of interaction between different actors involved, but also affect the way the EU learns to live within a perma-crisisresembling a 'boiling frog' syndrome to the point that the EU does not realise it exists within a crisis environment and becomes consumed by the crisis itself.…”
mentioning
confidence: 99%
“…Building on neo‐functionalism, historical institutionalism and experimentalism, Radaelli focuses on the role of ‘learning mechanism’ as a crucial passage between ‘crisis’ and ‘integration’: ‘… integration depends on how the EU learns in a crisis, and how learning brings the EU to the next crisis’. (Radaelli, 2022). Analytically, the model distinguishes between different types of crises, particularly ‘slow‐burning’ and ‘fast‐burning’ crises, pointing out that they tend to trigger different mechanisms of learning: ‘inferential’ and ‘contingent’ respectively.…”
mentioning
confidence: 99%